On Semantic Structure of Proper Nouns - Бирилло, Ж. (Kalbotyra, 1997)
The article deals with semantic problems of proper nouns. It tells about defining of the semantic structure of proper nouns through the informants associations. The author presents the results obtained through comparative analysis of the associations. The accent is laid on the regional qualities of the information, data, emotions, evaluations corresponding the given toponyms in both Lithuanian and Russian informants.